Pengaruh Konflik Pekerjaan Dan Keluarga Serta Konflik Keluarga Dan Pekerjaan Terhadap Totalitas Kerja : Kepribadian Extraversion Dan Conscientiousness Sebagai Variabel Moderator Pada Kementerian X - Lieke Puspasari; Yunita Faela Nisa (Epigram, 2020)
This study aims to determine the effect of work and family conflicts as well as family and work conflicts on work engagement, and personality extraversion and conscientiousness as moderator variables in ministries x. Through this research, it is expected to know the significance of the influence of work and family conflicts and family and work conflicts on the work engagement, and whether conscientiousness and extraversion personalities can be moderator variables for Ministry X employees. The population studied in this study was PNS Ministry X. this study amounted to 210 respondents. Data collection instruments using the Utrecht Work Engagement Scale (UWES) were developed by Schaufeli and Bakker, work and family conflicts and family and work conflicts developed by Netemeyer et al., 1996. This study uses a quantitative approach with multiple regression analysis methods, and validation testing construct using the Confirmatory Factor Analysis (CFA) technique. The research sample was determined using convenient sampling technique. The results of this study indicate that there is a significant influence of the variable influence of work and family conflicts as well as family and work conflicts on work engagement. Extraversion and conscientiousness personality also affect work totality. Extraversion personality does not moderate the relationship of work and family conflicts and family and work conflicts to the totality of work. So that Hypothesis 05 and Hypothesis 06 are accepted. Personality conscientiousness moderates the relationship of work and family conflict and family and work conflict to work engagement.